Evaluation of acute normovolemic hemodilution and autotransfusion in neurosurgical patients undergoing excision of intracranial meningioma - Imtiaz A Naqash; M A Draboo; Abdul Qayoom Lone; Showkat H Nengroo; Altaf Kirmani; Abdul Rashid Bhat (Wolters Kluwer Medknow Publications, 2011)
Background : Several blood conservation strategies have been tried with the purpose of reducing homologons blood transfusion. Patients & Methods : In a prospective randomized study, the potential benefits of acute normovolemic hemodilution (ANH) with autologous transfusion were investigated as a blood conservation technique in surgical excision of intracranial meningioma. Over a period of 2 years, 40 patients undergoing excision of intracranial meningioma were randomly assigned to two groups of 20 patients each. Group I (Control Group) received conventional homologous blood intraoperatively and were not subjected to ANH. In Group II (ANH Group), Acute Normovolemic Hemodilution was initiated to a target hematocrit of 30% after induction of anesthesia. Parameters studied included changes in hemoglobin, hematocrit and hemodynamic parameters. Results : The mean value of blood withdrawn in ANH group was 802.5 ± 208 ml. This was replaced simultaneously with an equal volume of 6% Hydroxyethyl starch to maintain normovolemia. There was no statistically significant variation in mean hemoglobin levels between the two groups at various stages of study. Hematocrit decreased significantly in both the groups at various stages as compared to preoperative values , the decrease being more but insignificant in group II. Changes in heart rate and mean blood pressure were similar and without statistically significant differences in either group at various stages of study. The amount of surgical blood loss in group I was 835.29 ± 684.37 ml, as compared to 865 + 409.78 ml in group II. The difference was statistically insignificant (p>0.05). The mean volume of homologous blood transfused in group I was 864.71 ± 349.89 ml, as compared to 165 ± 299.6 ml in group II which was statistically significant (p<0.05). In group II (ANH Group) only 5 patients (25%) required homologous blood whereas in group I I all patients (100%) needed homologous blood. Conclusion : We conclude that acute normovolemic hemodilution up to a target hematocrit of 30% is safe and effective in reducing the need for homologous blood in neurosurgical patients undergoing excision of intracranial meningioma.